Harnessing the power of social media for learning / Norazlin Abd Aziz and Nor Syamaliah Ngah - Abd Aziz, Norazlin; Ngah, Nor Syamaliah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Social media platforms engaged in learning gives educators a place to interact, communicate, and build professional learning communities. These virtual communities encourage communication, exchange of ideas, participation, and resource sharing between educators and act as a channel for encouragement, support, and companionship. By working together, we can improve the knowledge and abilities of educators, which is a type of continuous professional development. Online learning offers a useful additional path with its own set of benefits and limits, even though it cannot completely replace the advantages of in-person collaborations and discussions with peers. The use of social media platforms has become a vital tool in the modern educational and professional development landscape. Using these digital networks for professional learning offers several advantages that improve learning outcomes in addition to upending established educational paradigms. The many benefits of using social media for learning are examined in this essay.